Evolusi Epistemologi Ilmu dari Yunani hingga Posmodernisme dan Implikasinya terhadap Paradigma Pendidikan Kontemporer - Muhamad Ibnu Malik; N. Fitri Amaliya; Urwah Urwah; Imroatus Sholihah; Adang Hambali (Universitas Mathla'ul Anwar Banten, 2026)
This study examines the evolution of the epistemology of science from classical Greek thought, Islamic scientific tradition, empirical modernism, to relativistic postmodernism, and analyzes its implications for contemporary educational paradigms. The purpose of this study is to identify the epistemological character of each historical phase, find similarities and differences related to the sources and validity of knowledge, and formulate their influence on educational theory, learning approaches, and curriculum development in the modern and postmodern eras. This study uses a qualitative approach with a literature study method through the analysis of primary philosophical sources and secondary academic literature. Data are classified thematically and analyzed using content analysis techniques. The results show that Greek epistemology emphasizes rationality; Islamic epistemology is integrative between revelation, reason, and empiricism; modern epistemology prioritizes scientific empiricism and objectivity; while postmodern epistemology views knowledge as plural and contextual. The study concludes that these epistemological dynamics have a significant influence on educational paradigms. Modernism gave rise to objective and competency-based education; postmodernism gave rise to collaborative, contextual, and learner-centered learning; Meanwhile, Islamic epistemology offers an integrative paradigm that balances intellectual, empirical, and moral aspects. This research contributes theoretically as a cross-historical epistemological framework and practically as a reference for developing holistic and adaptive curricula and learning models.